â€œNYEPI SERIESâ€ THE ICON OF BALI AS HERITAGE DESTINATION IN THEME OF CULTURE EVENT? - Wiarti, Luh Yusni (Jurnal Perhotelan Undiksha, 2013)
ABSTRACTBali has a lot of potencies to be developed as one of world heritage destination. It has the tangible heritages and also the intangible ones. Bali has a lot of culture events, the inherited (old) events ones and also created ( new) events that are still continuing to do in the present time by present generation. As the tourism grows in Bali, the purpose of this paper is to investigate the tourism dimension that is related to the icon of Bali as Heritage Destination. Is the series of Nyepi will be suitable for an icon for Bali as Heritage Destination in Theme of Culture events? In this context, surveyed on 100 tourists were made (domestics and international) and analysed qualitatively by literature study to find out and prove the event that can be the icon of Bali as Heritage Destination.Keywords:; Heritage, Culture Heritage ,Events, Culture Event, Icon